THE PROBLEM OF NORMALIZATION AND STANDARDIZATION OF LANGUAGE IN ENGLISH AND UZBEK LINGUISTICS - Turgunov , Shukhratjon (Educational Research in Universal Sciences, 2023)
This article discusses the problems associated with language normalization and standardization efforts in English and Uzbek linguistics. It explains what language normalization and standardization entail and why linguists undertake such projects. The benefits and challenges of normalization are considered for both English and Uzbek. Historical contexts of standardization movements are provided for each language. Issues that arise from promoting a standard language at the expense of dialects and other forms of the language are examined. The article concludes by arguing that complete normalization is impossible to achieve and that diversity within languages should be maintained.